Вплив дресування на структуру і властивості гарячекатаної листової сталі для холодної штамповки - Куцова, Валентина Зіновіївна; Іванченко, Віталій Георгійович; Котова, Тетяна Володимирівна; Ковзель, Максим Анатолійович (НМетАУ, 2021)
UKR: Досліджено вплив дресування на структуру і властивості гарячекатаних сталевих штаб та листів, які призначені для холодної штамповки. Отримані дані можуть бути використані при визначенні параметрів дресування для забезпечення формування структури і рівня властивостей металу згідно з вимогами ГОСТ 4041–2017. Розробка оптимальної технології дресування дозволить знизити несприятливий вплив процесу старіння та отримати якісну листову сталь для холодної штамповки.

RUS: Исследовано влияние дрессировки на структуру и свойства горячекатаных стальных полос и листов, предназначенных для холодной штамповки. Установлено, что дополнительная дрессировка проката из стали 08кп и отжиг при температуре 600-800оС обеспечивает формирование уровня свойств и микроструктуру в соответствии с ГОСТ 4041–2017. Определено, что для получения необходимого комплекса механических свойств и микроструктуры в горячекатаном толстолистовом прокате из низкоуглеродистой кипящей стали необходимо, чтобы суммарная степень деформации перед отжигом превышала критическую. Исследовано влияние дрессировки на структуру и механические свойства горячекатаной листовой стали. Установлено, что с целью повышения пластичности горячекатаных полос и обеспечения уровня механических свойств металла и его структуры в соответствии с ГОСТ 4041–2017 целесообразно установить параметры дрессировки для получения качественной листовой стали для холодной штамповки.

ENG: We investigated the influence of skin-rolling on the structure and properties of hot-rolled steel strips and sheets for cold stamping. It has been established that skin-rolling of rolled steel made of 08кп steel and annealing at a temperature of 600-800°C provides the formation of properties and microstructure in accordance with ГОСТ 4041–2017. It was found that to obtain the required combination of mechanical properties and microstructure in hot-rolled plate made of low-carbon boiling steel, it is necessary that the total degree of deformation before annealing exceeds the critical one. Conclusion. We investigated the influence of tempering on the structure and mechanical properties of hot-rolled sheet steel. It has been established that in order to increase the ductility of hot-rolled strips and ensure the level of mechanical properties of the metal and structure in accordance with ГОСТ 4041–2017, it is advisable to skin-rolling stempering parameters to obtain high-quality sheet steel for cold stamping.
Влияние дрессировки на структуру и свойства горячекатаной листовой стали для холодной штамповки
Influence of Skin-Rolling on the Structure and Properties of Hot-Rolled Sheet Steel for Cold Stamping
В. Куцова: ORCID 0000-0003-2413-679X; М. Ковзель: ORCID 0000-0001-5720-1186
Keywords: дресування; гаряча прокатка; розмір зерна; механічні властивості; холодна штамповка; відпал; старіння; КМТОМ